2013
DOI: 10.2147/dddt.s43964
|View full text |Cite
|
Sign up to set email alerts
|

Novel phytochemical–antibiotic conjugates as multitarget inhibitors of Pseudomononas aeruginosa GyrB/ParE and DHFR

Abstract: BackgroundThere is a dearth of treatment options for community-acquired and nosocomial Pseudomonas infections due to several rapidly emerging multidrug resistant phenotypes, which show resistance even to combination therapy. As an alternative, developing selective promiscuous hybrid compounds for simultaneous modulation of multiple targets is highly appreciated because it is difficult for the pathogen to develop resistance when an inhibitor has activity against multiple targets.MethodsIn line with our previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…However, the biodistribution and metabolism profiles of the phytochemicals may not coincide with those of the antimicrobials, and thus challenging the antimicrobial–phytochemical combination therapies on whether the optimal therapeutic efficacy is really achieved. To overcome this obstacle, we adopted an in silico approach to design novel antimicrobial–phytochemical conjugate compounds (i.e., conjugate the active parts of antimicrobials and phytochemicals based on computer-aided molecular simulations) (Jayaraman et al, 2013). In the current study, we report the synthesis of a sulfamethoxazole–gallic acid conjugate (hybrid 1) and the evaluation of its antimicrobial activity against three bacterial stains purchased from the American Type Culture Collection (ATCC) and two E. faecalis clinical isolates (designated as isolates 1 and 2) from a Saskatchewan poultry farm.…”
Section: Introductionmentioning
confidence: 99%
“…However, the biodistribution and metabolism profiles of the phytochemicals may not coincide with those of the antimicrobials, and thus challenging the antimicrobial–phytochemical combination therapies on whether the optimal therapeutic efficacy is really achieved. To overcome this obstacle, we adopted an in silico approach to design novel antimicrobial–phytochemical conjugate compounds (i.e., conjugate the active parts of antimicrobials and phytochemicals based on computer-aided molecular simulations) (Jayaraman et al, 2013). In the current study, we report the synthesis of a sulfamethoxazole–gallic acid conjugate (hybrid 1) and the evaluation of its antimicrobial activity against three bacterial stains purchased from the American Type Culture Collection (ATCC) and two E. faecalis clinical isolates (designated as isolates 1 and 2) from a Saskatchewan poultry farm.…”
Section: Introductionmentioning
confidence: 99%
“…Including some degree of flexibility in the molecule may help the common and non-common pharmacophoric features to accommodate to the correspondent binding sites of the different intended targets; however, the degree of flexibility should be carefully tuned so that an excess of flexibility does not conspire against the binding affinity (owing to unfavorable entropic loss associated to the binding event) or the bioavailability of the drug (it should be remembered that many druglikeness rules limit the number of flexible bonds in the molecule). An illustrative example of some of these principles is provided by the recent research from Jayaraman et al (2013) . These authors applied the fragment-based approach in the design of phytochemical-antibiotic conjugates conceived as multivalent inhibitors of Pseudomonas aeruginosa DNA gyrase subunit B (GyrB)/topoisomerase IV subunit B, dihydrofolate reductase (DHFR) and dihydropteroate synthase (DHPS).…”
Section: Some Considerations Related To the Design And Screening Of Mmentioning
confidence: 99%
“…Recently interaction studies are drawn to study the associated effects of antibiotic and phytochemicals (Sakharkar et al, 2009; Jayaraman et al, 2013). A current study revealed that phytochemical-antibiotic conjugates have multitarget inhibitors of Pseudomononas aeruginosa GyrB/ParE and DHFR was extremely effective (Jayaraman et al, 2010).…”
Section: Phytochemicalsmentioning
confidence: 99%